Uji Organoleptik Mixed Fruit Yogurt dari Sari Buah Naga Merah (Hylocereus polyrhizus) – Pisang Ambon (Musa paradisiaca) dengan Berbagai Level Penambahan Stabilizer CMC (Carboxy Methyl Cellulose) - Siti Rahmawati Zulaikhah (Fakultas Peternakan, Universitas PGRI Kanjuruhan Malang, 2022)
The weakness of yogurt processing is the formation of syneresis, which will affect consumer preferences. Efforts to anticipate this used stabilizer, one of which is CMC (Carboxy Methyl Cellulose). The purpose of this study is to find out the influence of the addition of CMC stabilizer, the balance of red dragon fruit juice - ambon banana, and the interaction between the addition of CMC with the balance of red dragon juice - ambon banana to the sensory properties of mixed fruit yogurt. Research design using Randomized Group Design factorial pattern with 3 blocks or 3 replays. Factor 1) 4 cmc addition level 0%, 0.5%, 1% and 1.5% (b/v), factor 2) 3 red dragon juice balance: ambon banana (25:75, 50:50, and 75:25 with a total addition of 12%. Organoleptic testing of mix fruit yogurt was conducted by a rather trained panelist as many as 30 panelists for each block. The sensory test result data was analyzed with variance analysis, which was further tested with Duncan's new Multiple Ranges Test (DMRT). The variables observed in this sensory test are color, taste, texture, aroma and consumer preferences. The results showed that the addition of CMC influenced the sensory properties of taste, aroma texture and consumer preferences. The balance of red dragon fruit juice and banana ambon affects the sensory properties of colors, aromas and consumer preferences. There is no interaction between the addition of CMC with the balance of red dragon juice and banana ambon to the sensory properties of color, taste, texture and consumer preferences.